Evaluating the Levels of Mental Health Awareness in Higher Education Institutions - Baiq Anisya Nelahi Purnadya; Nurul Asmaya Fitria Hasanah; Baiq Oriza Januarlinda; Gunawan Gunawan (Indonesian Journal of Health and Medical Education, 2026)
Mental health awareness is a crucial issue in the higher education ecosystem, given the high academic, social, and personal pressures experienced by students. This study aims to analyze the level of student awareness of mental health in higher education through a survey titled "Mental Health Matters." The research method used a quantitative approach, distributing questionnaires to students from various study programs. Data were analyzed descriptively to describe students' knowledge, attitudes, and perceptions regarding mental health and the importance of accessing campus counseling services. The survey results indicate that most respondents have a good understanding of mental health, but still encounter barriers such as social stigma and a lack of openness in seeking professional help. These findings emphasize the need to improve mental health literacy, strengthen social support within the campus environment, and the role of higher education institutions in providing more accessible services. This research is expected to provide a basis for developing mental health promotion programs in higher education.